2020
DOI: 10.1109/access.2020.3024675
|View full text |Cite
|
Sign up to set email alerts
|

Hardware Acceleration for Container Migration on Resource-Constrained Platforms

Abstract: The computing capabilities of client devices are continuously increasing; at the same time, demands for ultra-low latency (ULL) services are increasing. These ULL services can be provided by migrating some micro-service container computations from the cloud and multi-access edge computing (MEC) to the client devices. The migration of a container image requires compression and decompression, which are computationally demanding. We quantitatively examine the hardware acceleration of container image compression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
(35 reference statements)
0
8
0
1
Order By: Relevance
“…Linguaglossa et al has proposed the extensive overview of the hardware architectures for network function virtualization (NFV) to provide abstractions for accessing components and physical resources into the ecosystem [25]. P. Shantharama et al have demonstrated the Intel QAT hardware acceleration that performs image compression and decompression and achieved high network bandwidth [26][27]. The work in [27] surveyed the emerging hardware platforms for executing softwarized network functions.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Linguaglossa et al has proposed the extensive overview of the hardware architectures for network function virtualization (NFV) to provide abstractions for accessing components and physical resources into the ecosystem [25]. P. Shantharama et al have demonstrated the Intel QAT hardware acceleration that performs image compression and decompression and achieved high network bandwidth [26][27]. The work in [27] surveyed the emerging hardware platforms for executing softwarized network functions.…”
Section: Related Workmentioning
confidence: 99%
“…P. Shantharama et al has surveyed the emerging hardware platforms for executing softwarized network functions. There are few works in [25][26][27] that provides a comprehensive survey of hardware accelerated platforms associated for architectural enhancement by reducing the core utilization and expanding the ISA and cache memory access. Table I shows the works carried out in various literature.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This facilitates reducing the complexity of the search process. Notably, we set an aspiration criterion: if the aspiration criterion is met, then the move is released (removed) from the Tabu list (Lines [16][17][18]. The aspiration criterion is defined for the case when a better solution than the current best solution is found.…”
Section: Algorithm 2: Tabu Searchmentioning
confidence: 99%
“…In order to accomplish the service migration, the VM and container migration schemes transfer: (i) the application states, i.e., the state information that the application itself generated (mainly the variable values of the counters and timers and other intermediate data that characterize the current functioning status of the application at a given time), and (ii) the VM or container states, i.e., the state information that the VM or container generated (e.g., the states of the operating system). The VM or container state information is typically an enormous amount of data, resulting in substantial delays for the MEC service migration with VM and container migration schemes [15], [16]. Furthermore, these VM and container migration schemes are not suitable for novel MEC use cases, such as vehicle platooning and tactile internet, which may require manipulations (e.g., splitting or merging) of the application states (e.g., when a truck leaves or rejoins a vehicle platoon).…”
Section: Introductionmentioning
confidence: 99%